2017
DOI: 10.1111/jpn.12697
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of grape seed cake inclusion in the diet of healthy fattening‐finishing pigs

Abstract: SummaryModulatory capacity of bioactive compounds from different wastes has been scarcely investigated in pigs. This study aimed to evaluate the effects of dietary inclusion of grape seed cakes (GS diet) on performance and plasma biochemistry parameters as health indicators, as well as on several markers related to inflammation and antioxidant defence in the liver of fattening-finishing pigs. Twelve cross-bred pigs (TOPIG) were randomly assigned to one of two experimental diets: control and 5% grape seed cake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 67 publications
(89 reference statements)
2
26
1
1
Order By: Relevance
“…GP diet increased TAS in both the colon and duodenum of piglets and this result is better than those of antioxidant capacity testing in the plasma of piglets fed grape seed and grape mark diet [ 55 ] or with plant extracts including grape seeds [ 31 ]. Also, Taranu et al (2018) registered no different TSA in comparison with the control in the liver of fattening pigs fed grape seed diet [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…GP diet increased TAS in both the colon and duodenum of piglets and this result is better than those of antioxidant capacity testing in the plasma of piglets fed grape seed and grape mark diet [ 55 ] or with plant extracts including grape seeds [ 31 ]. Also, Taranu et al (2018) registered no different TSA in comparison with the control in the liver of fattening pigs fed grape seed diet [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…TBARS-MDA is the main by-product of lipid peroxidation, and previous studies reported that the antioxidant compounds (flavonoids, phenols, PUFA) from grape extracts or grape by-products are able to control and diminish the TBARS level by their ability to scavenge free radicals [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations